Enhancing Indonesian Language Writing Skills Through the Arya Penangsang Animation - Pratama, Galih Cahya; Yuniawan, Tommi; Purwati, Panca Dewi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examined the use of Arya Penangsang animation as a culturally grounded instructional medium for improving Indonesian language writing skills among fifth-grade students at SDN Wonosemi 2. Writing instruction in elementary classrooms is often constrained by students' limited ability to generate ideas, organize paragraphs, and use appropriate vocabulary and sentence structures. A sequential explanatory mixed-methods design was employed. Quantitative data were obtained from pre-test and post-test writing scores of 23 students, while qualitative data were collected through classroom observation, documentation, and analysis of students' written products. Writing performance was assessed using three aspects: content relevance to the theme, paragraph coherence, and vocabulary and sentence structure. Descriptive quantitative findings showed an increase in the overall mean score from 64.78 in the pre-test to 82.17 in the post-test, with an absolute gain of 17.39 points. Aspect-level analysis also indicated improvement in content relevance, paragraph coherence, and vocabulary and sentence structure. Qualitative findings explained that the animation provided a concrete visual narrative, increased attention and motivation, supported idea generation, and helped students organize storylines more coherently. The integration of both strands suggests that Arya Penangsang animation is a feasible and pedagogically meaningful medium for culturally contextualized writing instruction. However, because the study used a small one-group sample without a control group, the findings should be interpreted as preliminary evidence of learning improvement and classroom feasibility rather than definitive causal evidence.